2011
DOI: 10.1021/ja200580x
|View full text |Cite
|
Sign up to set email alerts
|

Connection of Metallamacrocycles via Dynamic Covalent Chemistry: A Versatile Method for the Synthesis of Molecular Cages

Abstract: A modular approach for the synthesis of cage structures is described. Reactions of [(arene)RuCl(2)](2) [arene = p-cymene, 1,3,5-C(6)H(3)Me(3), 1,3,5-C(6)H(3)(i-Pr)(3)] with formyl-substituted 3-hydroxy-2-pyridone ligands provide trinuclear metallamacrocycles with pendant aldehyde groups. Subsequent condensation reactions with di- and triamines give molecular cages with 3, 6, or 12 Ru centers in a diastereoselective and chemoselective (self-sorting) fashion. Some of the cages can also be prepared in one-pot rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
92
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(95 citation statements)
references
References 144 publications
(45 reference statements)
2
92
0
1
Order By: Relevance
“…The successful diamination of xylene provides the simplest access to benzylic diamines, which are the important units in polyamides and molecular cages. [29,30] The above results clearly show the efficiency and generality of this amination method (Schemes 2 and 3). Next, the selectivity of the reaction was studied (Scheme 4).…”
supporting
confidence: 56%
“…The successful diamination of xylene provides the simplest access to benzylic diamines, which are the important units in polyamides and molecular cages. [29,30] The above results clearly show the efficiency and generality of this amination method (Schemes 2 and 3). Next, the selectivity of the reaction was studied (Scheme 4).…”
supporting
confidence: 56%
“…Severin and co-workers [198] reported that substituents at position 4 of the 3-hydroxy-2-pyridone ligand did not interfere with the self-assembly of (arene)Ru(II) complexes to produce trinuclear metallacycles. The com- .…”
Section: Scheme 31mentioning
confidence: 99%
“…One-pot reactions were feasible for preparing simple Scheme 32. Synthesis of the metallamacrocycles 91a-c and 92a,b [198]. a Scheme 33.…”
Section: Scheme 31mentioning
confidence: 99%
See 1 more Smart Citation
“…Such transformations can be triggered by external means, such as light, solvent, or chemical signals [84][85][86][87][88][89]. For Pt-based SCCs, this process exploits the same preference for heteroligation as is used in multicomponent assembly.…”
Section: Supramolecule-to-supramolecule Transformationmentioning
confidence: 99%